PENERAPAN MEDIA INTERAKTIF DALAM MENINGKATKAN MINAT DAN HASIL BELAJAR SISWA - Arman; Muh. Jalil Kamal (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The application of interactive media in an educational context has become an interesting and important topic in an effort to increase student interest and learning outcomes. Interactive media is digital technology that allows teachers to create a more interesting, dynamic and effective learning environment for students. The aim of this research is to explore how the application of interactive media can contribute to increasing student interest in learning and learning outcomes at various levels of education. Related studies have shown that the use of interactive media in learning has a significant positive impact. First, interactive media can increase students' interest in learning by presenting information visually, audio and interactively, which makes learning more interesting and challenging. Student involvement in interactive activities can also trigger higher learning motivation. Apart from that, the application of interactive media also has an impact on student learning outcomes. Through a more fun and interactive learning experience, students tend to be more active in understanding learning material and developing their cognitive skills. Interactive media also allows teachers to provide direct feedback, speeding up the learning process and increasing student understanding. Thus, the conclusion of this research is that the application of interactive media in education can be an effective strategy in increasing student interest in learning and learning outcomes. It is hoped that the integration of interactive media in the learning process can continue to be developed and improved to create a more adaptive, innovative and effective learning environment for students in this digital era.